Knowledge of Medical Students about Infant Feeding Practices - Muhammad Bilal Safdar, Muhammad Naveed, Mujahid Razzaq, Hafiz Muhammad Wasif, Anum Tahir, Mahwish Ejaz (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare medical student’s knowledge about breast feeding practices at the induction and exit from medical college. Study design: Comparative study Place and duration of study: Department of Pediatrics, University College of Medicine & Dentistry, The University of Lahore. Study was conducted from January 2019 to December 2019. Material and method: Total 200 students were enrolled, 100 from first year and 100 from final year class. Ethical approval was taken from ethical review committee data was collected on hand filled questionnaire. Results: There were 39.5% males and 60.5% female students. The ANOVA test of the variance was applied to compare the knowledge of first year and final year students. Final year students have a good knowledge regarding timing of initiation and pattern of breastfeeding whereas knowledge regarding advice of pre-lacteal, continuation of breastfeeding up to 6 months and frequency of complementary feeding for initial days was lacking in both first year and final year MBBS students. Conclusion: This study concludes that our curriculum has incorporated adequate knowledge regarding benefits of breast feeding, but the students lack practical knowledge and skills of counseling the parents about avoiding pre-lacteal feeds and promoting complementary feeding, that is also essential for child growth and development.